In-situ reduced MnO2 doped high-temperature proton exchange composite membrane, and preparation method and application thereof
Patent Information
- Application Number
- CN202611151152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-31
AI Technical Summary
该方案解决了传统物理共混法引入无机填料时易团聚、分布不均,以及传统磷酸掺杂PBI膜在200℃以上因磷酸脱水缩合导致质子传导能力下降和燃料电池性能衰减的问题,实现了无机相在聚合物基体内的均匀分散和有机/无机协同结构的构筑,并在高温条件下由MnPO4·H2O功能相提供额外质子传输通道并抑制磷酸脱水缩合,显著提升了超高温工况下的稳定运行能力
[0030]1)本发明所提供的复合膜将高价锰盐溶液与含耐热聚合物的溶液混合均匀得铸膜液后成膜并加热挥发溶剂,随后置于乙醇溶液中原位还原得低价锰氧化物聚合物膜,再通过磷酸掺杂原位生成MnPO4·H2O功能相的制备方法制得。该方案解决了传统物理共混法引入无机填料时易团聚、分布不均,以及传统磷酸掺杂PBI膜在200℃以上因磷酸脱水缩合导致质子传导能力下降和燃料电池性能衰减的问题,实现了无机相在聚合物基体内的均匀分散和有机/无机协同结构的构筑,并在高温条件下由MnPO4·H2O功能相提供额外质子传输通道并抑制磷酸脱水缩合,显著提升了超高温工况下的稳定运行能力;
Smart Images

Figure CN122659208B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a proton exchange membrane, and more particularly to an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, its preparation method, and its application, belonging to the field of high-temperature proton exchange membrane fuel cell technology. Background Technology
[0002] High-temperature proton exchange membrane fuel cells (HT-PEMFCs) typically operate at temperatures ranging from 120 to 300°C. They offer advantages such as lower requirements for hydrogen purity and rapid reaction kinetics, helping to reduce dependence on high-purity hydrogen and accelerate the development of the hydrogen energy industry. Currently, the mainstream proton exchange membrane in this field is a phosphoric acid (PA)-doped polybenzimidazole (PBI) membrane, whose working principle primarily relies on the physical blending of liquid phosphoric acid within the membrane to conduct protons. However, this operating mode presents a fundamental contradiction: achieving both mechanical properties and electrical conductivity is difficult. While a high phosphoric acid content ensures sufficient conductivity, it weakens the membrane's mechanical strength, and the liquid phosphoric acid is prone to continuous leakage during long-term operation, leading to performance degradation. To improve the dispersibility of inorganic fillers and enhance membrane performance, the industry commonly employs the method of introducing inorganic fillers into the PBI matrix.
[0003] The relevant literature (Zhang Qi, Pan Liyan, Xu Rong, et al. Preparation and characterization of high-temperature proton exchange membranes of graphene oxide / sulfonated polybenzimidazole [J]. Progress in Chemistry, 2018, 037(012):4758-4764.) discloses a scheme for preparing graphene oxide (GO) / sulfonated polybenzimidazole (SPBI) proton exchange composite membranes by blending and in-situ polymerization. This literature points out that in-situ polymerization allows GO to be more uniformly dispersed in the SPBI matrix, and the oxygen-containing functional groups on GO facilitate proton hopping in the composite membrane, thereby improving the proton conductivity of the composite membrane. Furthermore, the prepared composite membrane exhibits good water retention capacity and a high acid doping rate.
[0004] However, the above-mentioned solutions still have shortcomings. Although the literature improved the dispersibility of GO through in-situ polymerization, it was limited to a system of specific layered carbon materials and sulfonated polymers. For other common inorganic fillers (such as MnO2), there is still a lack of effective in-situ control methods. If commercial MnO2 is introduced into the polymer matrix using the traditional physical blending method, due to the large particle size and high surface energy of the filler, it is prone to agglomeration, sedimentation, and uneven dispersion in the matrix. This leads to insufficient reaction with phosphoric acid under high-temperature phosphoric acid (PA) doping conditions, usually only the surface part reacts, and the synergistic effect of inorganic fillers cannot be fully utilized. On the other hand, the upper limit of the test temperature reported in the literature is 160°C. Its composite membrane relies on the water retention capacity of the oxygen-containing functional groups of GO to assist proton conduction, but it does not cover operating conditions in higher temperature ranges. In contrast, under high-temperature conditions above 200°C, traditional phosphoric acid doped PBI membranes are prone to dehydration condensation reaction of phosphoric acid to form pyrophosphate, which leads to a significant decrease in proton conduction capacity and degradation of fuel cell performance. Furthermore, the inorganic fillers introduced by conventional physical blending serve only as physical reinforcing components, making it difficult to effectively control the microscopic chain arrangement of the polymer. This fails to meet the stringent requirements of the current industry for high-temperature proton exchange membranes to operate stably for a long time and maintain high proton conductivity under ultra-high temperature (above 200°C) conditions. Summary of the Invention
[0005] To address the problems of existing technologies, the first objective of this invention is to provide an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane. This composite membrane is prepared by uniformly mixing a high-valence manganese salt solution with a solution containing a heat-resistant polymer to obtain a casting solution, then heating to evaporate the solvent. Subsequently, it is in-situ reduced in an ethanol solution to obtain a low-valence manganese oxide polymer membrane, which is then prepared by in-situ generation of a MnPO4·H2O functional phase through phosphoric acid doping. This method solves the problems of easy agglomeration and uneven distribution of inorganic fillers introduced by traditional physical blending methods, as well as the decline in proton conductivity and fuel cell performance degradation of traditional phosphoric acid-doped PBI membranes above 200°C due to phosphoric acid dehydration condensation. It achieves uniform dispersion of the inorganic phase within the polymer matrix and the construction of an organic / inorganic synergistic structure. Furthermore, under high-temperature conditions, the MnPO4·H2O functional phase provides additional proton transport channels and inhibits phosphoric acid dehydration condensation, significantly improving stable operation under ultra-high temperature conditions.
[0006] The second objective of this invention is to provide a method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane. This method involves uniformly mixing a high-valence manganese salt solution with a solution containing a heat-resistant polymer to obtain a casting solution. After forming a film from the casting solution, the solvent is evaporated by heating to obtain a polymer film. Subsequently, the polymer film is in-situ reduced in an ethanol solution to obtain a low-valence manganese oxide polymer film. Then, a functional phase of MnPO4·H2O is generated in-situ through phosphoric acid doping. This method solves the problems of agglomeration, sedimentation, and uneven dispersion caused by traditional direct blending and doping of commercial MnO2, as well as the insufficient reaction between commercial MnO2 and phosphoric acid, where only the surface portion reacts. It enables uniform dispersion of MnO2 through in-situ nucleation and growth in the mPBI matrix, regulates the polymer chain spacing to form a stable and dense composite network structure, and allows for a complete reaction with phosphoric acid under high-temperature phosphoric acid doping conditions to generate a stable MnPO4·H2O functional phase with smaller particle size and more complete reaction. This phase remains stable at 220°C and inhibits phosphoric acid dehydration condensation, thereby significantly improving the ultra-high-temperature proton conduction performance of the composite membrane and the output performance of the fuel cell.
[0007] The third objective of this invention is to provide an application of an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, which is used in a high-temperature proton exchange membrane fuel cell.
[0008] To achieve the above-mentioned technical objectives, the present invention provides an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, comprising: uniformly mixing a high-valence manganese salt solution with a solution containing a heat-resistant polymer to obtain a casting solution; heating the casting solution to evaporate the solvent after forming a film to obtain a polymer film, which is then placed in an ethanol solution for in-situ reduction to obtain a low-valence manganese oxide polymer film, and then generating a MnPO4·H2O functional phase in-situ through phosphoric acid doping.
[0009] The technical solution provided by this invention uses high-valence manganese salt as a precursor to achieve molecular-level mixing in a polymer solution system. After film formation and solvent evaporation, low-valence manganese oxide is directly generated in the solid membrane matrix through ethanol reduction, allowing the inorganic phase to nucleate and grow in situ within the polymer network. This avoids the agglomeration and sedimentation caused by differences in filler size and surface energy in traditional physical blending. At the same time, the manganese oxide generated in situ in the subsequent phosphoric acid doping step reacts with phosphoric acid to form a functional phase of MnPO4·H2O, anchoring the proton carrier in the membrane through chemical bonds. This solves the problems of traditional PA / PBI membranes relying on liquid phosphoric acid for proton conduction, which leads to easy phosphoric acid loss and performance degradation caused by high-temperature dehydration condensation. This allows the membrane to maintain high proton conductivity and high structural stability even at ultra-high temperatures. If commercial MnO2 is directly blended without adopting this in-situ reduction scheme, the manganese oxide particles are large and prone to agglomeration and sedimentation. Not only is the dispersion uneven, but the reaction with phosphoric acid is also insufficient, with only the surface part reacting. It is impossible to effectively form the MnPO4·H2O functional phase, making it difficult to suppress the dehydration condensation of phosphoric acid at a high temperature of 220℃, and it is also impossible to provide additional proton transport channels, resulting in a significant decrease in high-temperature proton conductivity and battery performance.
[0010] As a preferred embodiment, the high-valence manganese salt is a permanganate and / or a manganate.
[0011] As a preferred embodiment, the heat-resistant polymer is a modified imidazole heat-resistant polymer.
[0012] This invention limits the manganese source to permanganate or manganate, utilizing their strong oxidizing and reducible properties. In an ethanol reduction system, these manganese can be quantitatively converted to MnO2 and uniformly dispersed within the membrane. Simultaneously, the polymer is limited to a modified imidazole heat-resistant polymer. Its rigid aromatic ring structure and the nitrogen atoms of the imidazole ring can form a hydrogen bond network with phosphate, providing a basic support for high-temperature proton conduction. Furthermore, compared to mPBI, the modified polymer exhibits greater molecular chain flexibility and solubility, which is beneficial for forming a fish-scale-like fracture morphology during liquid nitrogen quenching, thus adapting to the micropores and grain structure introduced by in-situ reduction and ensuring the overall performance of the membrane. If other manganese salts are used instead of permanganate, in-situ quantitative conversion cannot be achieved under mild ethanol reduction conditions, leading to incomplete reduction or uncontrollable product particle size. If mPBI is used instead of a modified imidazole heat-resistant polymer, its poor solubility makes it difficult to uniformly prepare the casting solution, increasing small particle defects in the membrane and affecting gas barrier properties and mechanical strength.
[0013] As a preferred embodiment, the preparation process of the modified imidazole heat-resistant polymer is as follows: after thoroughly mixing mPBI with anhydrous lithium salt in a solvent, the mixture is stirred at a constant temperature of 70~100℃ and 500~700r / min for 3~5h.
[0014] In the technical solution provided by this invention, anhydrous lithium salt is added to a polar aprotic solvent such as DMAC. The coordination between lithium ions and the nitrogen atoms of the imidazole ring on the mPBI molecular chain disrupts the hydrogen bonds between polymer molecular chains, effectively untangling the rigid aromatic ring polymer chains. This allows the polymer chains to fully dissolve and expand in the solvent, resulting in a homogeneous polymer solution. This facilitates subsequent molecular-level homogeneous mixing with high-valence manganese salt solutions and avoids MnO2 grain segregation after film formation due to localized concentration inhomogeneities. Without the addition of anhydrous lithium salt, mPBI exhibits poor solubility due to its rigid aromatic ring structure, resulting in undissolved particles in the casting solution and defects on the film surface after formation, leading to decreased gas barrier properties. If the stirring temperature is below 70°C or the stirring time is less than 3 hours, dissolution and untangling are insufficient, resulting in poor solution homogeneity. If the temperature is above 100°C or the stirring time is too long, excessive thermal motion of the polymer chains or excessive solvent evaporation may occur, affecting the quality of the casting solution.
[0015] As a preferred embodiment, the mass-to-volume ratio of solute to solvent in the casting solution is 0.025~0.05 g / mL, wherein the solute, based on the mass fraction of Mn element in mPBI, is 3~10%. This invention must strictly adhere to the above requirements, limiting the mass fraction of Mn element in mPBI to the range of 3~10%. This ensures a moderate content of in-situ generated MnO2, effectively controlling the polymer chain spacing from 3.70 Å to 3.47 Å to form a dense composite network, while avoiding excessive MnO2 content that leads to decreased membrane structural integrity and reduced gas barrier performance. If the mass fraction of Mn element is below 3%, the MnO2 content is insufficient, resulting in limited effects on chain spacing control and phosphate doping rate improvement, with no significant improvement in proton conductivity and battery performance. If it exceeds 10%, the MnO2 grains in the membrane are too large and numerous, causing the open-circuit voltage to drop to approximately 0.84 V, significantly reducing gas barrier performance, and consequently lowering battery output performance.
[0016] As a preferred embodiment, the solvent is at least one selected from DMAC, DMF, DMSO, NMP, and acetonitrile. More preferably, the solvent is DMAC. This invention specifies that the solvent is a polar aprotic solvent, capable of simultaneously dissolving mPBI and permanganate without reacting with the polymer backbone. If a polar aprotic solvent is not used, it may result in the inability to simultaneously dissolve the polymer and manganese salt, and may also lead to the solvent itself being oxidized by potassium permanganate, causing premature gelation of the system. It should be noted that even with a polar aprotic solvent, it is not absolutely stable to the permanganate system; the permanganate system will still slowly oxidize DMAC. Therefore, the permanganate solution and the polymer solution must be prepared separately, ready for immediate use.
[0017] As a preferred embodiment, the casting solution is used to form a film by coating a clean substrate with a coating height of 1000~1200μm, followed by vacuum drying to evaporate the solvent.
[0018] As a preferred embodiment, the vacuum drying conditions are: drying at 120~200℃ until the material reaches a constant weight.
[0019] As a preferred embodiment, the preparation process of the low-valent manganese oxide polymer membrane is as follows: the polymer membrane is immersed in an ethanol solution by volume, and then reduced in situ for 4-5 hours at 70-90℃ and 500-700 r / min, followed by drying. This invention uses ethanol as a reducing agent to reduce permanganate to MnO2 in situ. By controlling the above process parameters, the small and uniform size of the MnO2 crystals is ensured, without agglomeration or sedimentation. If the temperature is too low, the permanganate cannot be completely reduced within 4-5 hours, and residual high-valent manganese in the membrane will cause side reactions during phosphate doping. If the temperature is higher than 90℃, ethanol volatilization will intensify and may damage the membrane matrix.
[0020] As a preferred embodiment, the volume ratio of ethanol to deionized water in the ethanol solution is 1:1 to 3.
[0021] The concentration of ethanol also has a direct impact on the rate of in-situ reduction; both excessively high and low concentrations can lead to a decrease in the size and uniformity of MnO2 grains.
[0022] It is worth noting that, compared with directly loaded MnO2, in-situ generated MnO2 can not only ensure fine and uniform grain size, but also ensure its tight bonding with the membrane substrate, avoiding dissolution or detachment at high temperatures, thereby significantly improving the service life of the composite membrane.
[0023] As a preferred embodiment, the phosphoric acid doping process is as follows: the low-valence manganese oxide polymer film is immersed in phosphoric acid with a concentration of 80-85wt% at 50-70°C for 40-80 hours.
[0024] This invention controls the aforementioned process parameters to ensure that phosphoric acid fully penetrates the membrane and fills the micropores and gaps between polymer chains. Simultaneously, the in-situ generated MnO2 reacts with phosphoric acid to form the MnPO4·H2O functional phase. The bound water in this functional phase can decompose at high temperatures to provide additional protons (H+), and remains stable at 220°C. It is important to note that the in-situ generation of the MnPO4·H2O functional phase is due to the synergistic effect of the aforementioned process parameters. Arbitrarily changing these parameters, causing them to fall outside the aforementioned requirements, will not only prevent the formation of the MnPO4·H2O functional phase, but will also cause the phosphoric acid to dehydrate and condense into pyrophosphoric acid under subsequent high-temperature conditions, directly leading to a decrease in proton transport capacity.
[0025] The present invention also provides an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, obtained by any of the preparation methods described above.
[0026] The composite membrane provided by this invention has a uniformly dispersed inorganic phase of MnO2 and a functional phase of MnPO4·H2O inside. The polymer chain spacing is reduced from 3.70 Å to 3.47 Å to form a dense composite network. It also contains a micron-scale microporous structure introduced by in-situ reduction, which solves the problems of inorganic phase agglomeration and sedimentation and phosphoric acid dehydration condensation at high temperature in traditional blend membranes. This makes the membrane have high proton conductivity, high structural stability and ultra-high temperature operation capability.
[0027] This invention also provides an application of an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, which is used in a high-temperature proton exchange membrane fuel cell. The fuel cell using this composite membrane utilizes the properties of the MnPO4·H2O functional phase within the membrane to provide additional proton transport channels and suppress phosphoric acid dehydration condensation at high temperatures, enabling the battery to operate stably and continuously within a temperature range of 160~240℃. This solves the bottleneck problem of performance degradation in traditional PA / PBI membrane fuel cells above 200℃ due to phosphoric acid dehydration condensation.
[0028] As a preferred embodiment, the high-temperature proton exchange membrane fuel cell operates at a temperature of 160~240℃, with an anode gas flow rate of 300~400 sccm and a cathode gas flow rate of 300~400 sccm.
[0029] Compared with the prior art, the beneficial technical effects of the technical solution provided by the present invention are as follows:
[0030] 1) The composite membrane provided by this invention is prepared by uniformly mixing a high-valence manganese salt solution with a solution containing a heat-resistant polymer to obtain a casting solution, forming a membrane, heating to evaporate the solvent, and then reducing it in situ in an ethanol solution to obtain a low-valence manganese oxide polymer membrane. This membrane is then prepared by in-situ generation of a MnPO4·H2O functional phase through phosphoric acid doping. This method solves the problems of easy agglomeration and uneven distribution of inorganic fillers introduced by traditional physical blending methods, as well as the decline in proton conductivity and fuel cell performance degradation of traditional phosphoric acid-doped PBI membranes above 200℃ due to phosphoric acid dehydration condensation. It achieves uniform dispersion of the inorganic phase within the polymer matrix and the construction of an organic / inorganic synergistic structure. Furthermore, under high-temperature conditions, the MnPO4·H2O functional phase provides additional proton transport channels and inhibits phosphoric acid dehydration condensation, significantly improving stable operation under ultra-high temperature conditions.
[0031] 2) The preparation method provided by the present invention involves a three-step synergistic process: mixing a high-valence manganese salt solution with a solution containing a heat-resistant polymer to obtain a casting solution, reducing the film in situ with ethanol after film formation, and then generating a functional phase of MnPO4·H2O in situ through phosphoric acid doping. This achieves uniform dispersion of MnO2 in the mPBI matrix, control of polymer chain spacing, introduction of microporous structure, and construction of a high-temperature stable proton conduction structure.
[0032] 3) In the technical solution provided by this invention, the fuel cell using the above-mentioned composite membrane utilizes the characteristic that the MnPO4·H2O functional phase inside the membrane provides additional proton transport channels and inhibits phosphoric acid dehydration condensation at high temperatures, enabling the battery to operate stably and continuously within a temperature range of 160~240℃. Tests and Arrhenius curve fitting results show that proton transport in all membranes within the temperature range of 100~160℃ follows a skip transport mechanism, with activation energies of 10.61, 9.67, and 8.17 KJ·mol⁻¹, respectively. -1 The activation energy in the 160~200℃ range decreased significantly to 3.69, 1.98, and 1.65 KJ·mol⁻¹, respectively. -1 This indicates that the proton conduction mechanism has changed, with the MnPO4·H2O functional phase acting as a new proton conduction site to participate in the intramembrane proton migration process. This constructs a synergistic proton conduction structure that differs from the traditional PA / PBI system, providing the composite membrane with an additional proton transport channel besides liquid phosphoric acid. This solves the bottleneck problem of performance degradation of traditional PA / PBI membrane fuel cells at temperatures above 200°C due to phosphoric acid dehydration condensation. Attached Figure Description
[0033] Figure 1 The XRD patterns of the composite films prepared in Examples 1-3 and Comparative Examples 1-2 of this invention are shown below.
[0034] Figure 2 XPS spectra of the composite membranes prepared in Example 2 and Comparative Example 1 of this invention;
[0035] in, Figure 2 (a) is the full spectrum. Figure 2 (b) is the high-resolution spectrum of Mn 2p from Example 2. Figure 2 (c) is the high-resolution C1s spectrum of Example 2. Figure 2 (d) is the high-resolution C 1s spectrum of Comparative Example 1. Figure 2 (e) is the N 1s high-resolution spectrum of Example 2. Figure 2 (f) is the N 1s high-resolution spectrum of Comparative Example 1;
[0036] Figure 3 The images show the cross-sectional morphology and elemental distribution of the composite membrane samples prepared in Examples 1-3 and Comparative Examples 1-2 of this invention; wherein, Figure 3 (a) The mPBI membrane of Comparative Example 1, Figure 3 (b) The mPBI-M3.5 membrane of Example 1, Figure 3 (c) The mPBI-M7.5 membrane of Example 2, Figure 3 (d) The mPBI-M10 membrane of Example 3, Figure 3 (e) The mPBI-S7.5 membrane of Comparative Example 2, Figure 3 (a) ~ Figure 3In (e), each row from left to right represents the grayscale SEM cross-sectional image, the Mn element distribution image, and the N element distribution image, respectively.
[0037] Figure 4 mPBI-M prepared in Example 1 of this invention 3.5 Polarization curves and power density curves of composite membrane assembled fuel cells at different temperatures;
[0038] Figure 5 mPBI-M prepared in Example 2 of this invention 7.5 Polarization curves and power density curves of composite membrane assembled fuel cells at different temperatures;
[0039] Figure 6 mPBI-M prepared in Example 3 of this invention 10 Polarization curves and power density curves of composite membrane assembled fuel cells at different temperatures;
[0040] Figure 7 The graphs show the polarization curves and power density curves of the fuel cell assembled with the pure mPBI membrane prepared in Comparative Example 1 of this invention at different temperatures.
[0041] Figure 8 mPBI-S prepared for Comparative Example 2 of this invention 7.5 Polarization curves and power density curves of composite membrane assembled fuel cells at different temperatures;
[0042] Figure 9 This is a comparison graph showing the peak power density of fuel cells assembled with different composite membranes prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention as a function of temperature.
[0043] Figure 10 Line graphs showing the change in current density as a function of temperature for fuel cells assembled with different composite membranes prepared in Examples 1-3 and Comparative Examples 1-2 of this invention at 0.65V.
[0044] Figure 11 The electrochemical performance diagrams are shown for different composite membranes prepared in Examples 1-3 and Comparative Examples 1-2 of this invention.
[0045] in, Figure 11 (a) Proton conductivity diagrams of different composite films prepared in Examples 1-3 and Comparative Examples 1-2. Figure 11 (b) Arrhenius curves of different composite membranes prepared in Examples 1-3. Detailed Implementation
[0046] The technical solution of the present invention will be further described in detail below with reference to embodiments and comparative examples. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the process reagents used in the embodiments and comparative examples are all commercially available conventional products.
[0047] Example 1
[0048] This embodiment provides an in-situ reduction MnO2-doped high-temperature proton exchange composite membrane, the specific process of which is as follows:
[0049] Step S1: Place mPBI and anhydrous lithium chloride in sample bottle A at a mass ratio of 4:1 (i.e., 0.4 g mPBI and 0.1 g anhydrous lithium chloride), add 10 mL DMAC solvent, and stir at 600 r / min for 4 h in an oil bath at 80 ℃ to ensure that mPBI is fully dissolved.
[0050] Step S2: Weigh 0.0417 g of KMnO4 particles into sample bottle B according to the ratio of Mn element to mPBI mass fraction of 3.5%, add 3 mL of DMAC solvent, and sonicate for 2 h to completely dissolve KMnO4.
[0051] Step S3: Mix the solutions in sample vials A and B, and stir evenly in an oil bath at 40°C to prepare a casting solution; the mass-to-volume ratio of KMnO4 to solvent in this casting solution is 0.0417 g / 13 mL, approximately 0.0032 g / mL, and the solute is 3.5% based on the mass fraction of Mn element in mPBI;
[0052] Step S4: Set the hot stage temperature and the initial oven temperature to 40°C, apply the casting solution to a clean glass plate, and scrape the solution to a height of 1200μm. Then, place the casting solution that has been uniformly scraped onto the glass plate into a vacuum oven, set the oven temperature to 120°C and keep it at that temperature for more than 10 hours.
[0053] Step S5: Immerse the prepared solid polymer membrane in a reducing solution with a volume ratio of ethanol to deionized water of 1:2, and stir at 80°C for 4 hours to reduce KMnO4 to MnO2 in the solid membrane matrix and allow it to nucleate and grow in situ. After drying, the mPBI-M3.5 membrane is obtained.
[0054] Step S6: Cut the mPBI-M3.5 membrane into 3cm×3cm pieces and soak them in 85wt% phosphoric acid solution at 60℃ for 48h to dope with phosphoric acid, so that the phosphoric acid can fully penetrate into the membrane and fill the micropores and gaps between polymer chains; the in-situ generated MnO2 reacts with phosphoric acid at a high temperature above 160℃ to generate the MnPO4·H2O functional phase, and obtain the PA / mPBI-M3.5 composite membrane.
[0055] Furthermore, the present invention also utilizes the above-mentioned composite membrane to prepare a corresponding fuel cell, the process of which is as follows:
[0056] Preparation of gas diffusion electrodes (GDEs): 40 mg of Pt / C catalyst (40 wt%, John Matthey) was added to 4 mL of deionized water and stirred to moisten. Then, 16 mL of isopropanol was added to disperse it into a slurry. 260 mg of 5 wt% PBI-DMSO solution was added to the slurry, and the solid content of the catalyst slurry after mixing was 0.2–0.25%. After ultrasonic dispersion for 40 minutes, the uniform catalyst ink was ultrasonically sprayed onto carbon paper, with the Pt loading controlled at 0.9 mg·cm⁻¹. -2 Then, it was heated to 80°C in a tube furnace under a nitrogen atmosphere for 40 minutes.
[0057] Assembly: Using a 2 wt.% PBI-DMSO solution as a binder, the PA / mPBI-M3.5 composite membrane was directly assembled between two GDE sheets to form a membrane electrode assembly without hot pressing. The active area of the membrane electrode was 4 cm². 2 .
[0058] The composite membrane prepared in this embodiment was subjected to XRD testing, such as... Figure 1 As shown, the broad diffraction peak of the mPBI-M3.5 membrane near 2θ≈25° is further broadened and shifted towards higher angles compared to the pure mPBI membrane. Based on the Bragg equation, its average interchain spacing (dsp) is calculated to be 3.61 Å, while that of the pure mPBI membrane is 3.70 Å. This indicates that the in-situ generated MnO2 can effectively regulate the internal microstructure of the membrane, making the polymer chains more tightly arranged and forming a more stable and dense composite network structure. Polarization curve tests were performed on the fuel cell assembled with the composite membrane in this embodiment under the following conditions: single-cell operating temperature 160~240℃, and anode pure hydrogen flow rate 350 sccm·min. -1 Cathode pure oxygen flow rate 400 sccm·min -1 No humidification or back pressure was required. Test results showed that the fuel cell assembled with this mPBI-M3.5 membrane had an open-circuit voltage greater than 0.90 V, exhibiting good gas barrier performance and membrane integrity. Figure 4 As shown, the polarization and power density curves of the mPBI-M3.5 membrane gradually increased with increasing temperature in the range of 160–240 °C, and the proton conductivity reached 57.4 mS·cm at 200 °C. -1 The results showed that the micron-scale microporous structure introduced by in-situ reduction provided more space for phosphoric acid to be contained, thus reducing the proton conduction resistance.
[0059] Example 2
[0060] This embodiment is exactly the same as Embodiment 1, except that: 0.0933 g of KMnO4 particles are weighed with Mn element accounting for 7.5% of the mass fraction of mPBI, and 5 mL of DMAC solvent is added; accordingly, the mass-volume ratio of solute to solvent in the casting solution in step S3 is changed; the resulting composite membrane is denoted as mPBI-M7.5.
[0061] XPS analysis was performed on the mPBI-M7.5 membrane prepared in this embodiment, as follows: Figure 2 As shown in the full spectrum, in addition to C and N elements, the pure mPBI membrane of Example 2 also showed obvious O and Mn element signals in the full spectrum. In the C 1s and N 1s high-resolution spectra, both Example 2 and the pure mPBI membrane exhibited the same CC, CN, and C=N characteristic peak structures, indicating that the in-situ reaction process did not damage the main chain structure of the mPBI polymer. The Mn 2p spectrum also showed Mn 2p... 3 / 2 The region exhibits characteristic peaks at 643.0 eV and 641.5 eV, corresponding to Mn, respectively. 4+ and Mn 3+ Species, and Mn 4+ The peak area was the highest, and combined with XRD results, it was confirmed that potassium permanganate had undergone an in-situ transformation reaction within the membrane to generate MnO2. SEM and EDS analyses of the membrane cross-section were performed, such as... Figure 3 As shown, all cross-sections of the mPBI polymer membranes exhibit a fish-scale morphology, and in Example 2, the fish-scale pattern on the membrane cross-section becomes denser with increasing KMnO4 addition. EDS analysis of Mn shows that in Example 2, Mn is distributed uniformly across the entire membrane cross-section, without any obvious large-scale aggregation regions. Compared to Comparative Example 2, where the direct addition of commercial MnO2 resulted in Mn concentration at the bottom of the membrane and significant agglomeration, the MnO2 crystals generated by in-situ reduction in this example are smaller and more uniformly dispersed.
[0062] The composite membrane-assembled fuel cell prepared in this embodiment was subjected to polarization curve testing under the same conditions as in Example 1. Figure 5 and Figure 9 As shown, Example 2 exhibits the best overall performance, achieving a peak power density of 1620 mW·cm² at 220°C without humidification or back pressure. -2 The performance was significantly higher than that of pure mPBI membranes and commercial MnO2 blend membranes, and continued to improve within the 220~240 °C range, breaking through the bottleneck of performance degradation in traditional PA / PBI systems under ultra-high temperature conditions. Figure 10 As shown, under 0.65V conditions, Example 2 exhibited a higher current density output than Comparative Example 1 throughout the entire test temperature range, reaching a current density of 1.120 A·cm at 230 °C.-2 In contrast, Comparative Example 1 was only 0.946 A·cm. -2 Proton conductivity tests showed that the mPBI-M7.5 membrane had a proton conductivity of 72.8 mS·cm at 200 °C. -1 The proton conductivity curves from 100 to 200 °C were piecewise fitted using the Arrhenius equation, and the activation energy was found to be 9.67 kJ·mol⁻¹ in the range of 100 to 160 °C. -1 The activation energy was significantly reduced to 1.98 kJ·mol⁻¹ in the 160–200 °C range. -1 This indicates that the proton conduction mechanism changes after 160℃, and the MnPO4·H2O functional phase participates in the intramembrane proton migration process as a new proton conduction site, constructing a synergistic proton conduction structure that is different from the traditional PA / PBI system, providing the composite membrane with an additional proton transport channel in addition to liquid phosphoric acid.
[0063] Example 3
[0064] This embodiment is exactly the same as Embodiment 1, except that: 0.1278 g of KMnO4 particles are weighed with Mn element accounting for 10% of the mass fraction of mPBI, and 5 mL of DMAC solvent is added; accordingly, the mass-volume ratio of solute to solvent in the casting solution in step S3 is changed; the resulting composite membrane is denoted as mPBI-M10.
[0065] The composite membrane prepared in this embodiment was subjected to XRD testing, such as... Figure 1 As shown, the diffraction peak of the mPBI-M10 film near 2θ≈25° shifts further to higher angles, and the average interchain spacing (dsp) decreases to 3.47 Å, indicating that with the increase of potassium permanganate addition, the polymer interchain spacing further decreases, and the chain arrangement becomes more compact. Figure 3 As shown, the fish-scale pattern on the cross-section of the mPBI-M10 membrane is further refined, the Mn element is densely and uniformly distributed, and the blue signal is significantly enhanced, indicating that the MnO2 generated by in-situ reduction is uniformly dispersed in the polymer matrix. However, due to the excessive amount of potassium permanganate added, the MnO2 grains in the membrane are too large and too numerous, resulting in a decrease in membrane structural integrity and a reduction in gas barrier performance. Fuel cell tests show that the open-circuit voltage of the mPBI-M10 membrane-assembled cell is approximately 0.84 V, lower than that of Examples 1, 2, and Comparative Example 1, and the output performance is lower than that of Examples 1 and 2, indicating that when the mass fraction of Mn element exceeds 10%, the overall performance of the membrane actually decreases.
[0066] Nevertheless, the mPBI-M10 membrane exhibits outstanding proton conductivity, reaching 85.4 mS·cm at 200°C. -1 It is 2.1 times the proton conductivity of a pure mPBI membrane at the same temperature. For example... Figure 6 As shown, the power density curve of the mPBI-M10 membrane continues to increase with increasing temperature in the range of 160~240℃, with a peak power density approaching 1500 mW·cm at 240℃. -2 Using the Arrhenius equation for fitting, the activation energy in the range of 100–160 °C is 8.17 kJ·mol⁻¹. -1 The activation energy in the 160~200℃ range is further reduced to 1.65 kJ·mol⁻¹. -1 This indicates that with the increase of KMnO4 addition, the microporous structure introduced by in-situ reduction further reduces the proton conduction resistance, and the MnPO4·H2O functional phase provides a more significant additional proton transport effect.
[0067] Comparative Example 1
[0068] This comparative example provides an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, the preparation process of which is as follows:
[0069] Step S1: Add 0.4 g mPBI and 0.1 g anhydrous lithium chloride to 10 mL DMAC, and stir for 4 h on an oil bath heating and stirring table at 80℃ and 600 r / min to fully dissolve mPBI and obtain casting solution.
[0070] Step S2: Set the hot stage temperature and the initial oven temperature to 40°C, apply the casting solution to a clean glass plate, and scrape the coating height to 1200μm; then place it in a vacuum oven, set the oven temperature to 120°C and keep it at that temperature for more than 10 hours to ensure that DMAC is fully volatilized.
[0071] Step S3: Boil the prepared membrane in deionized water at 80°C several times to completely remove residual DMAC solvent and anhydrous lithium chloride; finally, dry the membrane to obtain the mPBI membrane.
[0072] Using the same phosphoric acid doping conditions (85wt% phosphoric acid, 60℃, 48h) and membrane electrode assembly conditions as in Example 1, a PA / mPBI composite membrane was obtained and tested for fuel cells under the same conditions as in Example 1.
[0073] like Figure 7 and Figure 9 As shown, the open-circuit voltage of the fuel cell assembled with pure mPBI membrane is greater than 0.90 V. However, at temperatures above 200°C, due to the dehydration condensation of phosphoric acid to form pyrophosphate, the proton conductivity decreases, and the peak power density of the cell decreases with increasing temperature, making it unable to maintain high-performance output under ultra-high temperature conditions. Figure 10 As shown, under 0.65 V conditions, the current density of the mPBI film at 230 °C is only 0.946 A·cm⁻¹. -2This is significantly lower than the 1.120 A·cm in Example 2. -2 Proton conductivity tests showed that the proton conductivity of the mPBI membrane at 200℃ was only about 1 / 2.1 that of the mPBI-M10 membrane. In Comparative Example 1, the dehydration condensation of phosphoric acid at high temperatures resulted in a lower inflection point temperature for proton conductivity decay and the inability to provide additional proton transport channels, leading to a continuous decline in high-temperature performance.
[0074] Comparative Example 2
[0075] This comparative example provides an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, the preparation process of which is as follows:
[0076] Step S1: Add 0.0513 g of commercial nano-MnO2 to 10 mL of DMAC and ultrasonically disperse for 1 h to obtain solution A;
[0077] Step S2: Add 0.4 g mPBI and 0.1 g anhydrous lithium chloride to solution A, and stir for 4 h on an oil bath heating and stirring table at 80℃ and 600 r / min to obtain casting solution;
[0078] Step S3: Set the hot stage temperature and the initial oven temperature to 40°C, apply the casting solution to a clean glass plate, and scrape the coating height to 1200μm; then place it in a vacuum oven, set the oven temperature to 120°C and keep it at that temperature for more than 10 hours to ensure that DMAC is fully volatilized.
[0079] Step S4: The prepared membrane is boiled several times in deionized water at 80°C to completely remove residual DMAC solvent and anhydrous lithium chloride; finally, the membrane is dried to obtain the mPBI-S7.5 membrane. This comparative example did not undergo ethanol reduction treatment because nano-manganese dioxide was directly doped into the PBI membrane, eliminating the need for reduction.
[0080] Using the same phosphoric acid doping conditions and membrane electrode assembly conditions as in Example 1, a PA / mPBI-S7.5 composite membrane was obtained and tested in a fuel cell under the same conditions as in Example 1.
[0081] like Figure 3 As shown, the cross-sectional morphology of the mPBI-S7.5 membrane is not significantly different from that of the pure mPBI membrane. However, the EDS distribution of Mn elements shows that commercial MnO2 agglomerates and settles at the bottom of the membrane, with much worse dispersibility than the MnO2 generated by in-situ reduction. Figure 8 and Figure 9 As shown, the open-circuit voltage of the fuel cell assembled with the mPBI-S7.5 membrane is greater than 0.90 V, but its overall output performance is the lowest, with a peak power density of only about 1200~1300 mW·cm at 240℃. -2 It is significantly lower than 1620 mW·cm in Example 2. -2To verify the changes of manganese oxide under high-temperature conditions, 20 mg of commercial MnO2 was weighed and mixed with 0.1 mL of PA, placed in a polytetrafluoroethylene container, and heated to 160 °C in a tube furnace for 4 h. After the reaction, the product was removed, ground, and XRD was tested. The results showed that only the diffraction peaks at 2θ = 18.2°, 19.0°, 25.3°, 27.2°, 30.1°, and 35.6° in the XRD of the commercial MnO2 after the reaction corresponded to the standard PDF card of MnPO4·H2O, while the diffraction peaks at 2θ = 22.2°, 37.2°, 40.7°, 42.6°, 56.5°, and 67.4° all corresponded to commercial MnO2. Moreover, the MnO2 peak was stronger than that of MnPO4·H2O, indicating that the reaction between commercial MnO2 and PA was incomplete, and only a portion of the surface reacted. In contrast, the MnO2 produced by reduction with KMnO4 has smaller particle size and more uniform dispersion, and the reaction is more complete under the same reaction conditions. Its XRD pattern shows sharp peaks, which correspond well to the MnPO4·H2O standard PDF card #44-0071, and no residual MnO2 characteristic peaks were observed, indicating that the generated MnPO4·H2O has high crystallinity. Further heating of this material to 220℃ and holding for 6 h revealed that the product was still MnPO4·H2O, indicating that the MnPO4·H2O functional phase remains stable at 220℃, and the presence of bound water inhibits the dehydration condensation of PA at high temperatures. The mPBI-S7.5 membrane, due to the uneven dispersion of commercial MnO2 and insufficient reaction with PA, cannot effectively form the MnPO4·H2O functional phase. At high temperatures, the dehydration condensation of phosphoric acid leads to a lower inflection point temperature for proton conductivity decay, resulting in continuous performance degradation.
[0082] As demonstrated by the above embodiments and comparative examples, the in-situ reduction of MnO2 in this invention achieves uniform dispersion of MnO2 in the mPBI matrix. SEM-EDS characterization results of Examples 1-3 show that the MnO2 grains generated by in-situ reduction are smaller and more uniformly distributed along the film thickness direction, with no Mn agglomeration. In contrast, in the mPBI-S7.5 film of Comparative Example 2, which uses commercially available MnO2 directly doped, Mn elements only agglomerate and settle at the bottom of the film, exhibiting significantly worse dispersion than the MnO2 generated by in-situ reduction. The in-situ generated MnO2 further enhances structural regulation, gradually reducing the polymer chain spacing from 3.70 Å to 3.47 Å, resulting in a more compact polymer chain arrangement and a more stable and dense composite network structure, thereby improving the structural stability and phosphoric acid retention capacity of the film.
[0083] Furthermore, the in-situ generation of MnO2 and the in-situ generation of MnPO4·H2O functional phase via phosphoric acid significantly improved the proton conductivity of the composite membrane. Specifically, the mPBI-M10 membrane achieved a proton conductivity of 85.4 mS·cm at 200 °C. -1The proton conductivity is 2.1 times that of a pure mPBI membrane at the same temperature. Arrhenius curve fitting results show that all membranes in the 100–160 °C range follow a hopping transport mechanism, with activation energies of 10.61, 9.67, and 8.17 kJ·mol⁻¹, respectively. -1 The activation energy in the 160–200 °C range decreased significantly to 3.69, 1.98, and 1.65 kJ·mol⁻¹, respectively. -1 This indicates that the proton conduction mechanism has changed, with the MnPO4·H2O functional phase acting as a new proton conduction site to participate in the intramembrane proton migration process. This constructs a synergistic proton conduction structure that differs from the traditional PA / PBI system, providing the composite membrane with an additional proton transport channel besides liquid phosphoric acid.
[0084] Furthermore, the fuel cell using the composite membrane provided by this invention exhibits excellent transmission performance at ultra-high temperatures. Specifically, the fuel cell assembled in Example 2 (mPBI-M7.5) achieves a peak power density of 1620 mW·cm³ at 220 °C under conditions of no humidification and no back pressure. -2 Furthermore, the current density continued to increase within the 220–240 °C range, significantly exceeding that of the pure mPBI membrane in Comparative Example 1 and the commercial MnO2 blend membrane in Comparative Example 2. At 0.65 V, Example 2 achieved a current density of 1.120 A·cm⁻¹ at 230 °C. -2 In contrast, Comparative Example 1 was only 0.946 A·cm. -2 This indicates that the in-situ MnO2 / MnPO4·H2O composite structure constructed in this invention can effectively improve the proton conduction capacity and battery output capacity of the membrane material under high temperature conditions, break through the bottleneck of performance degradation of the traditional PA / PBI system under ultra-high temperature conditions, and show good engineering application prospects.
Claims
1. A method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, characterized in that, include: The permanganate solution is mixed evenly with the solution containing the heat-resistant polymer to obtain the casting solution; after the casting solution is used to form a film, the solvent is evaporated by heating to obtain a polymer film, which is then placed in an ethanol solution for in-situ reduction to obtain a low-valence manganese oxide polymer film, and then MnPO4·H2O functional phase is generated in-situ by phosphoric acid doping. The heat-resistant polymer is a modified imidazole heat-resistant polymer; The preparation process of the modified imidazole heat-resistant polymer is as follows: after thoroughly mixing mPBI with anhydrous lithium salt in a solvent, the mixture is stirred at a constant temperature of 70~100℃ and 500~700r / min for 3~5h. The mass-to-volume ratio of solute to solvent in the casting solution is 0.025~0.05 g / mL, wherein the solute is 3~10% based on the mass fraction of Mn element in mPBI.
2. The method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane according to claim 1, characterized in that: The solvent is at least one of DMAC, DMF, DMSO, NMP, and acetonitrile.
3. The method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane according to claim 1, characterized in that: The process of forming a film with the casting solution is as follows: the casting solution is coated onto a clean substrate with a coating height of 1000~1200μm, and then vacuum dried to evaporate the solvent, thus obtaining the film; the vacuum drying conditions are: drying at 120~200℃ until the material has a constant weight.
4. The method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane according to claim 1, characterized in that: The preparation process of the low-valent manganese oxide polymer membrane is as follows: the polymer membrane is immersed in an ethanol solution by volume, reduced in situ at 70~90℃ and 500~700r / min for 4~5h, and then dried to obtain the final product; the volume ratio of ethanol to deionized water in the ethanol solution is 1:1~3.
5. The method for preparing an in-situ reduced MnO2-doped high-temperature proton exchange composite membrane according to claim 1, characterized in that: The phosphoric acid doping process is as follows: the low-valence manganese oxide polymer film is immersed in phosphoric acid with a concentration of 80-85wt% at 50-70℃ for 40-80 hours.
6. An in-situ reduced MnO2-doped high-temperature proton exchange composite membrane, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.
7. The application of the in-situ reduced MnO2-doped high-temperature proton exchange composite membrane as described in claim 6, characterized in that: The composite membrane is used in a high-temperature proton exchange membrane fuel cell.
8. The application of the in-situ reduced MnO2-doped high-temperature proton exchange composite membrane according to claim 7, characterized in that: The high-temperature proton exchange membrane fuel cell operates at a temperature of 160~240℃, with an anode gas flow rate of 300~400 sccm and a cathode gas flow rate of 300~400 sccm.
Citation Information
Patent Citations
Phosphoric acid doped polybenzimidazole high-temperature proton exchange membrane and preparation method thereof
CN119890375A
Proton exchange membrane and preparation method and application thereof
CN119890376A